ON p-STATISTICAL CONVERGENCE OF ORDER a OF SEQUENCES OF SETS - Aral, Nazlim deniz; Kandemir, Hacer sengul; Et, M. I. K. A. I. L. (Univ Miskolc Inst Math, 2023)
In this paper we introduce the concepts of Wijsman p-statistical convergence of order a and Wijsman strongly p-convergence of order a. In addition, some inclusion theorems are also presented.
Keywords: statistical convergence; Wijsman convergence; sequences of sets